The sustainability of the European social model: EU governance, social protection and employment policies in Europe (Cheltenham, 2015)
"Highly valued by its citizens, the European social model is a defining feature of Europe and the European Union yet is under threat from the effects of both globalisation and the aftermath of the financial crisis. The Sustainability of the European Social Model addresses this issue in light of the current crisis that changed the landscape. It examines how social Europe responds to uncertainties that affect its development from a range of different disciplinary perspectives. The book begins by analysing interactions between EU law and national policies from a comparative perspective, highlighting the legal, social and institutional complexities that constrain the development of 'social Europe' It assesses the sustainablibity of EU law and policies in the areas pensions and employment policy and then focuses on two crucial areas of EU social policy: the regulations on working time and the provisions of social services of general interest.The expert contributors compare the experiences of a range of member states (and also bring in external comparison) to explore topics such as ageing, job quality, social protection and employment policies, social dialogue and the relationship between the various methods of European policy-making such as the 'community method' and the Open Method of Co-ordination. The analyses show that sustainability of the European social model will depend heavily on addressing failings in European governance. Insightful and comprehensive, this book is a detailed and timely resource for academic researchers. Its practical, policy-oriented insights into important issues in social and employment policy, as well as into European policy-making itself, will also be of great interest to practitioners and policy-makers."